Study of Benign And Malignant Masses of Cervix Using Various Modes of Transvaginal Ultrasound - Pattabiraman, Suhasini; Pattabiraman, Suhasini; P. Dhande, Rajasbala (International Journal of Psychosocial Rehabilitation, 2020)
Background - Out of all the pelvic masses that affect women, cervical masses make up for 8% of them with cervical cancer taking a higher precedence over the other cervical masses In this study, we will be using various applications of the transvaginal probe to evaluate usefulness of transvaginal ultrasound as a screening tool. Aims: To diagnose evidence of cervical mass lesions at an early stage and differentiate it into benign and malignant variety for better prognosis. Methodology: in the cross – sectional study in a rural Indian population with 92 married women having symptoms arising from cervical pathology or clinically suspected cases of cervical masses participating in the study and data collected by the Aloka Hitachi USG Machine Arietta S70 with high frequency transvaginal probe (4 - 8 MHz) with elastography. Results: after appropriate statistical analysis, we expect to find that those who will have benign features of cervical masses on B – mode and Colour Doppler corresponding with an SR of more than 3.4 in patients and a Tsukuba Score of ≤ 3 will be classified as benign masses of cervix. And similarly in lesions showing malignant properties on B – mode and Colour Doppler, we expect them to show an SR of more than 8.7 and Tsukuba Score of ≥ 4 will be classified as a malignant mass of cervix with histopathological correlation as gold standard. Conclusions: Ultrasonographic study of the masses of cervix could be used as a screening test to evaluate patients presenting with primary complaints associated with cervical pathologies to help differentiate benign from malignant masses of the cervix and detect early stages of cervical cancer which can alter disease progression and therefore prognosis post-treatment.